Parathyroid adenoma in pregnancy: A case report and systematic review of the literature - Pliakos, I.; Chorti, A.; Moysidis, Moysis; Kotsovolis, G.; Kaltsas, T.; Pana, A.; Ioannidis, A.; Papavramidis, TS. (Frontiers in Endocrinology, 2022)
Objective: Primary hyperparathyroidism is a common disorder of the parathyroid glands. Parathyroid adenoma (PA) in pregnancy is a relatively rare disease, which diagnosis and treatment is a challenging task. The aim of the present study is to present a new case of parathyroid adenoma during pregnancy and to give a detailed account of all reported cases of parathyroid adenoma during pregnancy in the literature Study Design: A bibliographic research was performed and characteristics of parathyroid adenomas in pregnancy such as age, gestational week at diagnosis, ionized calcium levels, genetic testing result, symptomatology, radiological method of localization, treatment method, gestational week at operation and maternal/ fetal complications were recorded. Results: A 34-years-old woman at her 25 weeks' gestation was diagnosed with parathyroid adenoma and was referred to our Surgical Department due to contraindication for conservative treatment. A parathyroidectomy was performed and the maternal and fetal postoperative period was uneventful. 211 cases of parathyroid adenoma in pregnancy were recorded in the literature and statistical analysis was perfomed. Median gestational week at diagnosis was 21 ±9.61 weeks. Mean level of ionized calcium was 2.69 mmol/L [SD=0.75, (2.55-2.84 95%CI)]. Most cases were familiar (72.4%), while surgery was the preferred treatment option (67.3%). The majority of cases were asymptomatic (21.7%) and the main radiological method applied for localization was ultrasound (63.4%). Conclusion: Parathyroid adenoma in pregnancy is a rare condition. The early diagnosis is of great importance as surgical treatment at the second trimester of pregnancy outweighs the maternal and fetal risks.